Kinerja Keuangan Dan Kemaslahatan Stakeholder Bank Umum Syariah Di Indonesia Periode 2010-2014 - Ariska Oktavia; Imron Mawardi (Universitas Airlangga, 2016)
The purpose of this research is to know the effect of financial performance to stakeholder’s maslahah on Sharia Commercial Bank in Indonesia. The exogenous latent variable that is used is financial performance which is formed by five indicators that are ROA, BOPO, NPF, FDR and CAR. The endogenous latent variable is stakeholder’s maslahah which is formed by five indicators: proprietor’ maslahah, employee’s maslahah, government’s maslahah, society’s maslahah, and consumer financing’s maslahah.Technique of analysis that is used is Partial Least Square (PLS) which is appropriate to relate latent variables. There are nine Sharia Commercial Banks which are appropriate to be taken as samples. The length of observation of this research is five years, from 2010 to 2014.The result of this research shows that business performance has positive and significant effect to stakeholder’s maslahah. It means that the rise of business performance will increase stakeholder’s maslahah.